1998
DOI: 10.1016/s1074-7613(00)80578-6
|View full text |Cite
|
Sign up to set email alerts
|

Arrest of B Lymphocyte Terminal Differentiation by CD40 Signaling: Mechanism for Lack of Antibody-Secreting Cells in Germinal Centers

Abstract: Despite extensive research, the role of CD40 signaling in B cell terminal differentiation remains controversial. Here we show that CD40 engagement arrests B cell differentiation prior to plasma cell formation. This arrest is manifested at a molecular level as a reduction in mRNA levels of secretory immunoglobulin gene products such as mu(s) and J chain as well as the loss of the transcriptional regulator BLIMP-1. Furthermore, the inhibition of B cell differentiation by CD40 engagement could not be overcome by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
114
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 41 publications
15
114
0
Order By: Relevance
“…This phenomenon is considered to regulate the effector T cell functions for B cell help as a negative feedback mechanism, and may play a role for determining the magnitude of the immune response (35). Furthermore, CD40L down-regulation seems to be necessary to mount normal immune responses, because prolonged CD40 signaling results in early abolition of the GC reaction (42,43). The down-regulation of ICOSL triggered by interaction with ICOS may be important for similar reasons to the CD40 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is considered to regulate the effector T cell functions for B cell help as a negative feedback mechanism, and may play a role for determining the magnitude of the immune response (35). Furthermore, CD40L down-regulation seems to be necessary to mount normal immune responses, because prolonged CD40 signaling results in early abolition of the GC reaction (42,43). The down-regulation of ICOSL triggered by interaction with ICOS may be important for similar reasons to the CD40 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A number of experimental observations, including the immune deficiency disorder in humans associated with CD40L deficiency, have demonstrated the importance of CD40-CD40L in humoral immunity (6 -13, 15-17, 35-38). Initial studies focused on the role of CD40 signaling of the B cell following engagement with CD40L from the T helper cell (11)(12)(13)(14)(15)(16)(17). A number of in vitro experiments have demonstrated the impact of CD40 signaling of the B cell, in combination with cytokines, on several steps along the pathway of B cell response, such as proliferation and Ig secretion (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies focused on the role of CD40 signaling of the B cell following engagement with CD40L from the T helper cell (11)(12)(13)(14)(15)(16)(17). A number of in vitro experiments have demonstrated the impact of CD40 signaling of the B cell, in combination with cytokines, on several steps along the pathway of B cell response, such as proliferation and Ig secretion (12)(13)(14)(15)(16)(17). Other more complex steps in B cell development, such as germinal center formation, somatic hypermutation, and creation of memory, clearly require CD40L-CD40, as demonstrated by murine models in which these pathways are inhibited by germline mutations, infusion of blocking Abs, or soluble receptors (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10). However, it has been shown that continued CD40 signaling in activated B cells prevents terminal differentiation as measured by a decrease in both secretory Ig and the transcriptional regulator B lymphocyte-induced maturation protein 1 (30). Together, these studies suggest that CD154 expression is critical for regulating the immune response at early and late times after activation.…”
Section: A Complex Containing Polypyrimidine Tract-binding Proteinmentioning
confidence: 95%